PENERAPAN KOMPRES DINGIN (ICE GEL) TERHADAP PENURUNAN NYERI LUKA EPISIOTOMI PADA PASIEN POST PARTUM DI RSUD Dr. SOESELO KABUPATEN TEGAL - Ita Nur Itsna; Anggun Larasati (STIKES BHAMADA SLAWI, 2022)
This study aims to determine the application of cold compress (ice gel) to reduce episiotomy wound pain in post partum patients at RSUD Dr. Soeselo Tegal Regency. This research method is a descriptive method with the research design being a case study. The results of the case study study with cold compress therapy (ice gel) had a significant influence in reducing the scale of pain in post partum patients with episiotomy wound pain. There was a decrease in the pain scale of the two respondents, namely the level of the pain scale before being given cold compress therapy (ice gel) in patient 1 pain scale 6 and patient 2 pain scale 7, after being given cold compress therapy (ice gel) for 3 days to both patients the pain scale dropped to 2. The application of cold compress (ice gel) is recommended to be done 3 times a day for 3 days with a duration of 5-10 minutes at a temperature of 15o C to reduce pain. In conclusion, cold compress therapy (ice gel) can reduce episiotomy wound pain in post partum patients.Keywords : Pain, Episiotomy, Cold Compress.